STUDY AND DESIGN OF PORTABLE ANTIMICROBIAL WATER FILTER - Batra, Shivani; Adhikari, Priyanka; Ghai, Anchit; Sharma, Aman; Sarma, Rhea; V, Suneetha (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â  Â Objective: This study was conducted to design a portable antimicrobial water filter which is both economic and easy to use. Methods: A prototype following the designing of the water filter was constructed. Layers of sand, cloth, activated charcoal, and cotton containing compartments were built for carrying out water analysis. Results: Most probable number index of Vellore Institute of Technology lake water was compared with that of filtered water. Complete water analysis was done, and the sand filter layer was observed to be responsible for a maximum of the antimicrobial action of the filter. Conclusion: The study demonstrated that the proposed design of water filter is efficient in removal of turbidity, odor, and microbial content of lake water along with decreasing the acidity of water.